Pelatihan Pembuatan Pupuk Kompos pada Ibu-ibu PKK Desa Tanjung Barepan Cawas Klaten - Nugroho, Anwari Adi; Hanik, Nur Rokhimah; Wiharti, Tri; Ayu Fitriani, Rindi Diah; Syafitri, Dewi (Universitas Pahlawan Tuanku Tambusai, 2025)
The majority of PKK mothers in Tanjung Barepan Cawas village are housewives, they need additional income. In the dry season, soybean waste in Cawas is abundant and is only used as animal feed, it can be processed into compost, as an alternative family income. The purpose of this service is to provide training in making compost. Providing skills in applying compost to planting media. The methods used are lectures, questions and answers, and practice. The target of this training is to increase understanding of how to make compost by 20%, and the results of the skills are very good. The results of the training can be concluded, there was an increase in understanding of the process of making organic compost from an average value of 38.23 to 89.14, (153.04%). The value of skills in making compost and its application to media and plants was 88.92 and 88.71, meaning that all participants are skilled in making fertilizer and its application to plants. Compost making activities and the like still need to be carried out, because they have many benefits for residents in increasing skills and family income.